Application of non-destructive techniques on a varve sediment record from Vouliagmeni Coastal Lake, Eastern Gulf of Corinth, Greece - Emmanouilidis, Alexandros; Unkel, Ingmar; Seguin, Joana; Keklikoglou, Kleoniki; Gianni, Eleni; Avramidis, Pavlos (Applied Sciences, 2020)
During the last few decades, X-ray attenuation systems have been established as standard techniques in geosciences and as excellent scientific tools for the analysis of sedimentary facies and structures. In the present study, we use two non-destructive and high-resolution systems (computed tomography, X-ray fluorescence) to address all sedimentological facies and structural characteristics on a 6 m long, partly laminated sediment record, from Vouliagmeni lake, located at the eastern part of the Corinth Gulf, Greece. Vouliagmeni lake is the deepest coastal lake in Greece, and its location is of great importance since it is located in one of the most tectonically active regions in the world. The chronological framework of the retrieved sediment sequence spans the last 12,000 years, with alternations of laminated and non-laminated sections. The annual accumulation of the laminated sequences was determined through the radionuclide concentration of 14 samples. Scanning tomography was performed with a medical CT scanner and a μCT scanner, aiming to compare the potentials and variations of both methods. Lamination boundaries, event layers (turbidites) and sediment deformations were distinguished through processing the extracted 3D rendered volumes, after applying ranges depending on Hounsfield (HU) values. Microscopic analysis revealed three main layer types in the varve sequences that were examined, attributing to summer/spring, autumn and winter deposits. Statistical analysis of the elemental composition, magnetic susceptibility (MS) measurements and HU values revealed three clusters/facies, reflecting climatic and in-lake hydrological changes. Cluster A emulates sedimentation during arid conditions, while Cluster B reflects humid conditions with increased precipitation and erosion. Cluster C represents sequences with homogenous Ca-rich sediment. Our proposed workflow highlights the possible correlation between the non-destructive variables that were measured, but also the variations and applications of each method and software used during this study.
Gesehen am 17.02.2025